Progression in Tobacco Use in India: An Application of Survival Function Analysis - Singh, Shri Kant; Kashyap, Gyan Chandra (International Journal of Social Sciences and Management, 2016)
Today India is the second largest producer of tobacco in the world and the third largest consumer. The World Health Organization predicts that tobacco deaths in India may exceed 1.5 million annually by 2020. The purpose of the present study to evaluate the pattern and correlates of tobacco use and quitting tobacco among smokers as well as users of smokeless tobacco. This study is based on the data from the Global Adult Tobacco Survey, India (2009-10). The study used the cox's proportional hazards regression model and Kaplan-meier survival analysis for computing the probability of quitting tobacco. Three level multilevel logistic regression model have been used to carry out the pattern and correlates of tobacco use. The highest percentage of young people currently using tobacco product in the North-eastern states of India. The hazard of quitting tobacco among female is 1.35 times (p